BRAC Lirnb and Brace Fittrng Centre (BLBC): annual report, September 2000-August 2001 - BRAC (© BRAC, 2016)
1. Introduction 2. Goals and objectives 3. Project elements 4. Services and products 5. Set up of the centre 6. Staff recruitment 7. Staff training 8. BLBC patient profile 9. Financing 10. Cost recovery